Building Positive Character, Negative Effects Environmental Protection and Wisdom Local Culture by the Applying of Full Day Schools in Rural Areas (Research Action in Public Senior High School of Lahat South Sumatra) - Ahmad Nasihin Paryono; Oktarini Oktarini (International Journal of Educational Management and Innovation, 2023)
Many schools in the city choose Full Day (FDS) but for schools in rural still in very little in the list to apply this. The research was action research of discovering whether increased positive impact in the positive character, security environment wisdom exposed to negative and local culture can be accomplished by applying the Full Day School program. This research aims to find the effect of applying rural FS at the school. The research results show that the first Full Day school (FDS) in a rural area school can maximize time to communicate with students to build good character, such as religious, social,l and environmental care to students. Secondly, FDS in rural school areas can protect students from bad effects outside the school environment, negatively influencing drug users, environment-free sex, bad motorcycle groups,  etc. Third, FDS gives students enough opportunity to learn about local culture with family and society about local culture. They can have time with their families from morning till noon on Saturday and Sunday, which would improve their knowledge of local culture and family activities. It can be concluded that FDS in rural school areas positively affects building positive and good student character. It is recommended that it be applied in other schools.